Discovering concrete in the 'Land of Stone': a pre-inventory of buildings constructed using proprietary reinforced concrete systems in Scotland c.1900-1920 - Borden, Allison H (The University of Edinburgh, 2007)
Although concrete is not traditionally considered an historic building material, the first example of its use dates from 5600 B.C. Types of concrete developed between that time and the late 19th century varied widely in terms of their individual admixtures, as well as in terms of their strength and durability characteristics. ‘Although the Romans experimented with bronze reinforcement’, it wasn’t until inventors rediscovered reinforcing techniques in the mid-19th century that the stage was set for the development of what is considered modern ‘concrete’, or reinforced concrete. In the United Kingdom and on the Continent, developments in reinforced concrete technology remained unchecked until just before the First World War, when the first governmental attempts to regulate use of the material took place. Reinforced concrete components and construction techniques during this period were all proprietary, or patented, technologies. Although approaches to marketing the technologies differed, companies marketing a product which incorporated their unique reinforcement into building frames and structures of their own design were selling ‘monolithic’ building systems. These are the subjects of this paper.
Keywords: reinforced concrete; Scotland; Hennebique; early 20th century